The Influence of Digital Learning Media Nearpod on The Motivation and Academic Achievement of Elementary School Students - Widodo Pujo Bintoro; Eges Triwahyuni; Ahmad Zaki Emyus (Journal of Education Technology)
This research is motivated by the low motivation of elementary school students, which also impacts their learning achievement. Low learning motivation is caused by the lack of supporting media for learning activities. The purpose of this study was to analyze the significant effect of the use of Nearpod digital learning media on elementary school students' learning motivation and learning achievement. The study used the Quasi Experiment method with a nonequivalent pretest-posttest control group design. The data collection method used questionnaires and tests. The instruments used were motivation questionnaires and learning achievement tests. The data analysis technique used inferential statistics with the t-test. Based on the results of the study, it can be concluded that the use of Nearpod digital learning media has a significant effect on elementary school students' motivation and learning achievement. This is evidenced by the analysis results showing that the tcount for the motivation and learning achievement variables is greater than the ttable, which means that the alternative hypothesis is accepted. Nearpod, with interactive and multimedia features, increases student involvement in the learning process, which ultimately positively impacts understanding concepts and academic achievement. This study implies that the application of Nearpod digital learning media has a positive impact on elementary school students' motivation and learning achievement.